Cost‐Effective Biomass Carbon/Calix[4]Quinone Composites for Lithium Ion Batteries. Issue 23 (28th November 2019) - Huang, Weiwei; Zhang, Meng; Cui, Huamin; Yan, Bing; Liu, Yang; Zhang, Qichun
Abstract: Searching for new cheap encapsulating materials to decrease the solubility of organic small molecules as the cathode materials in electrolytes and improve the performance of organic lithium‐ion batteries (LIBs) is very important and highly desirable. In this research, we found that a novel cheap biomass carbon (named as PPL), prepared by pyrolyzing calyxes of Physalis Peruviana L, can efficiently encapsulate calix[4]quinone to form composites, which can be used as cathodes in LIBs. The initial discharge capacity of the as‐fabricated battery was 437 mAh g −1 and could maintain 228 mAh g −1 after 100 cycles. Even at 1 C, the discharge capacity was still 217 mAh g −1 . Abstract : A novel type of conductive porous carbon PPL, prepared by pyrolyzing the calyxes of Physalis Peruviana L, can capsulate C4Q. The as‐obtained C4Q/PPL composites have been demonstrated as efficient cathodes in lithium‐ion batteries that displayed excellent cycle stability and coulombic efficiency.